The pseudophosphatase STYX targets the F‐box of FBXW7 and inhibits SCFFBXW7 function. (15th March 2018) - Reiterer, Veronika; Figueras‐Puig, Cristina; Le Guerroue, Francois; Confalonieri, Stefano; Vecchi, Manuela; Jalapothu, Dasaradha; Kanse, Sandip M; Deshaies, Raymond J; Di Fiore, Pier Paolo; Behrends, Christian; Farhan, Hesso
Abstract :